A Psychoanalytic Criticism of Ifesinachi Nwadike’s How Morning Remembers The Night - Olaniyan, Kolawole Dennis; Owoeye, Omolara Kikelomo (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
In recent times, it appears Nigerian poets are influenced by changes in the country’s social-political and economic landscape to such an extent that their artistic expressions are thought to have tilted towards psychological dimension. This observation transcends the social commitment and ideological inclinations often identified with the poets in the past. Therefore, this paper attempts a psychoanalytic criticism of Ifesinachi Nwadike’s poetry, How Morning Remembers the Night, focusing on the instances of psychosocial disorder as an association of socio-economically induced psychological conditions that find expression in the collection. Conceptualising this condition, the study adopts a descriptive research method premised on critical analysis in which attention is given to symptomatic elements like the persona’s recollected experiences, tone and cathartic disposition. Here, a synthesis of the theoretical paradigms of psychoanalysis proposed by Sigmund Freud and Erich Fromm is found rewarding in providing a framework for the conception of the poetry as the persona’s dream text. The study discovers that the psychosocial disorders identified in the collection symptomatically find expression in the poetic persona’s tone in form of emotional disturbances and that they are triggered by memories of societal failings. Consequently, the persona displays the identities of an aggrieved songbird and a griot whose memory is clouded by grief and anguish in reaction to societal foibles. The paper concludes that certain psychosocial disturbances that are noticeable among Nigerian citizens under the same unfavorable societal conditions have permeated Nwadike’s poetry.